MANAJEMEN PEMBELAJARAN TANFÎZH ALQUR’AN PADA PONDOK PESANTREN DI PROVINSI LAMPUNG - Akmansyah, Abdul Hamid, Muhammad (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2018)
This article intends to discuss the learning management of Tanfîzh al-Qur’an at Islamic Boarding Schools in Lampung Province. Teaching and learning activities need the planning, organizing, implementing and controlling actio. These management functions play a crucial role to  perfect learning tahfizh al-Qur’an. This is qualitative research while data collected through observation, interviews, and documentation. Data analyzed by reduction, presentation, and conclusion. Research concluded that the management functions have been carried out on tahfizh al-Qur’an in Islamic boarding schools, but at different intensities. In the planning aspect, generally they do not have written planning as in other formal schools or madrasah. In the organization of teaching materials, teaching strategies and learning media, all of them have in common. And with regard to the learning strategies they use the same principles of memorizing, depositing, and repeating memorization, even though in each boarding schools they have different terms, but same in principle.Keywords: Management, Learning, Tanfîzh Al-Qur’an